2019
DOI: 10.1103/physrevapplied.11.054052
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Fermi-Level Splitting of Cu -Poor and Cu -Rich CuInS2

Abstract: Cu(In, Ga)S 2-based solar cells are interesting tandem partners for Si or chalcopyrite solar cells, but suffer from a low open-circuit voltage. Recently, record efficiencies have been achieved by using higher growth temperatures for the absorber. To understand the effect of higher growth temperatures, we investigate the structural and electronic properties of CuInS 2 absorbers. By investigating the absorber alone as opposed to complete solar cells, we can separate changes in the absorber from effects of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 27 publications
5
41
0
Order By: Relevance
“…The band edge emission will be discussed using the data of the sample with Cu/In ratio of 1.8 as it shows the highest intensity and the best-resolved emissions. This suggests an improvement in the crystalline quality of the stoichiometric chalcopyrite phase when films are grown under Cu excess, as already found in our previous work [15]. In Fig.…”
Section: A Band Edge Emissionssupporting
confidence: 86%
See 1 more Smart Citation
“…The band edge emission will be discussed using the data of the sample with Cu/In ratio of 1.8 as it shows the highest intensity and the best-resolved emissions. This suggests an improvement in the crystalline quality of the stoichiometric chalcopyrite phase when films are grown under Cu excess, as already found in our previous work [15]. In Fig.…”
Section: A Band Edge Emissionssupporting
confidence: 86%
“…Recently, we showed that a deep defect in CuInS 2 with a luminescence around 0.8 eV is a major recombination center. We could demonstrate that the concentration of this defect is reduced with higher deposition temperature and higher Cu content [15,16].…”
mentioning
confidence: 80%
“…However, it did not translate into an increase in the device V oc due to interface losses. 5 Recently, we found that the improvement in QFLS for Cu-rich absorbers was mainly due to higher doping (D.A. et al, unpublished data).…”
Section: Context and Scalementioning
confidence: 93%
“…4 Therefore, sulfide chalcopyrite Cu(In,Ga)S 2 , due to its variable band gap between 1.5 and 2.4 eV, is receiving considerable interest as the absorber in the top cell of a tandem device. [5][6][7][8][9] Cu(In,Ga)S 2 adopts the chalcopyrite structure similar to high-efficiency Cu(In,Ga) Se 2 . Despite the high photoconversion efficiency (PCE) of 23.35% achieved using Cu(In,Ga)(S,Se) 2 , 10,11 the certified record PCE of pure sulfide Cu(In,Ga)S 2 solar cells remained limited to 15.5% thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The Na atomic % content in high‐temperature glass is less than half the one in SLG, and the K atomic % content is more than an order of magnitude lower than SLG. We have to use higher temperatures for the sulfide absorbers because it was shown that temperature is a critical parameter for sulfide absorbers 2,20 . Otherwise, we try to keep the processes as similar as possible, in particular by using one‐stage processes for all absorbers investigated.…”
Section: Preparation and Treatment Of Solar Cells And Characterizatiomentioning
confidence: 99%